2010
DOI: 10.1111/j.1467-8330.2009.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating “Streets for All” in Urban Transport Planning: The Case for Pedestrians, Cyclists and Street Vendors in Nairobi, Kenya

Abstract: This paper uses the concept of “streets for all” as the analytical basis to critique the neglect of pedestrians, cyclists and street vendors in transport policy and practice in the city of Nairobi. The paper shows that transport planning in Nairobi has not adequately taken care of informal economy and non‐motorized transport such as walking and cycling. This has resulted in competing use of pavements and roads, exposing pedestrians, cyclists and street vendors to insecurity and harassment. The paper calls for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…5, 6 Ogendi is with the School of Public Health and Community Development, Maseno University, Maseno, Kenya; Odero is with the School of Medicine, Maseno University, Maseno, Kenya; Mitullah is with the Institute of Development Studies, University of Nairobi, Nairobi, Kenya; Khayesi is with the Department of Injuries and Violence Prevention, World Health Organization, Geneva, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…5, 6 Ogendi is with the School of Public Health and Community Development, Maseno University, Maseno, Kenya; Odero is with the School of Medicine, Maseno University, Maseno, Kenya; Mitullah is with the Institute of Development Studies, University of Nairobi, Nairobi, Kenya; Khayesi is with the Department of Injuries and Violence Prevention, World Health Organization, Geneva, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Aligula et al, (2005) reported that 49% of daily trips in Nairobi were either on foot or bicycle. However, bicycle use was limited by safety concerns (especially over lack of bicycle lanes) (Khayesi et al, 2010). Another 42% of trips used minibuses or other forms of public transport, while 9% were made in private vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Social inclusion is increasingly presented to be a basic condition for achieving sustainable urban transport (Khayesi, Monheim, & Nebe, 2010;Lucas, 2012;World Bank, 2013). Although it is conceptually differentiated from social exclusion (Labonte, 2004), it arguably offers a basis for problematizing the plight of individuals and groups that are excluded by transport systems (Church et al, 2000;Lucas & Musso, 2014).…”
Section: Problematizing Transport Exclusion Through Social Inclusionmentioning
confidence: 99%
“…This is because its ensuing negative social representation (Khayesi et al, 2010;Pochet & Cusset, 1999) prohibits transport planning in its current form from allocating street-spaces that can facilitate its use. At the same time, cycling stands no chance for inclusion in commodified spaces because it generates no economic return that is readily quantifiable using the current transport evaluation tools such as the Cost-Benefit Analysis (Jones, Moura, & Domingos, 2013).…”
Section: In Search Of Inclusion In Excluded Spaces and Processesmentioning
confidence: 99%
See 1 more Smart Citation